Application of Pyroligneous Acid as a Plant Growth Stimulant Can Improve the Nutritional Value of Soybean Seed - Randi Noel; Michael J. Schueller; James Guthrie; Richard A. Ferrieri (Crops)
Farmers today are using biochemical treatments to improve their crop yields. Commercialized organic biostimulants exist in the form of pyroligneous acid generated by burning agricultural waste products. During the 2023 growing season, we demonstrated that soil treatment with a commercial pyroligneous acid product, Coriphol™, manufactured by Corigin Solutions, Inc., stimulated plant growth and significantly improved yield with an optimal treatment dose of 2 gal. acre−1. In the present work, we examined the effect of this treatment on soybean nutritional content using seed harvested from the 2023 season. Total mean seed protein content for untreated control plants was 32.26 ± 0.49% of dry mass and increased 10.8% to 35.64 ± 0.64% with treatment. This increase resulted in a net reduction in total free amino acid content, although levels of the essential dietary amino acid, lysine, were boosted 6-fold. Total lipid content was unaffected by treatment with mean levels of 21.61 ± 0.70% of dry mass noted. Treatment, however, reduced saturated fatty acid content by roughly 40%, and reduced the polyunsaturated content of linoleic acid in favor of the monounsaturated fatty acid, oleic acid. Finally, Coriphol™ treatment did not impact seed content of eight essential micronutrients including Na, Mg, K, Ca, Fe, Ni, Cu, and Mo, but did significantly boost Zn and Mn levels. Altogether, these results demonstrate that soil treatment with the growth stimulant Coriphol™ has the potential to improve the dietary nutritional value of soybean.